2021
DOI: 10.1007/s10549-021-06271-y
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of Flap Endonuclease 1 (FEN1) in breast ductal carcinoma in situ

Abstract: Background Impaired DNA repair mechanism is one of the cancer hallmarks. Flap Endonuclease 1 (FEN1) is essential for genomic integrity. FEN1 has key roles during base excision repair (BER) and replication. We hypothesised a role for FEN1 in breast cancer pathogenesis. This study aims to assess the role of FEN1 in breast ductal carcinoma in situ (DCIS). Methods Expression of FEN1 protein was evaluated in a large (n = 1015) well-characterised cohort of DCIS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…FEN1 inactivated the P53 signaling pathway by recruiting ubiquitin specific protease 7 (USP7) to prevent the ubiquitination and degradation of murine double minute 2 (MDM2). Further analysis of clinical samples also found that high expression of FEN1 was associated with aggressive tumor behavior and may directly play a role in the progression of carcinoma in situ to aggressive disease [ 63 ]. TGF-β 1 was found to promote epithelial mesenchymal transformation (EMT) phenotype through the up-regulation of FEN1 and down-regulation of MiR-140-5p, leading to the metastasis of HCC cells [ 64 ].…”
Section: The Role Of Fen1 In Diseasesmentioning
confidence: 99%
“…FEN1 inactivated the P53 signaling pathway by recruiting ubiquitin specific protease 7 (USP7) to prevent the ubiquitination and degradation of murine double minute 2 (MDM2). Further analysis of clinical samples also found that high expression of FEN1 was associated with aggressive tumor behavior and may directly play a role in the progression of carcinoma in situ to aggressive disease [ 63 ]. TGF-β 1 was found to promote epithelial mesenchymal transformation (EMT) phenotype through the up-regulation of FEN1 and down-regulation of MiR-140-5p, leading to the metastasis of HCC cells [ 64 ].…”
Section: The Role Of Fen1 In Diseasesmentioning
confidence: 99%
“…Flap endonuclease 1 (FEN1) exhibits multiple values in the early diagnosis [ 1 , 2 ], targeting therapy [ 3 , 4 , 5 , 6 ], and prognostic monitoring [ 7 , 8 ] of various cancers. Traditional assays, including western blot, reverse transcription-polymerase chain reaction (RT-PCR), and enzyme-linked immunosorbent assay (ELISA) [ 1 , 3 , 4 ] had already been utilized to detect FEN1.…”
Section: Introductionmentioning
confidence: 99%